Synthesis of caffeine/Poly (vinyl alcohol) polymer with UV-protection properties - Trujillo Galarza, José Ignacio (2023)
A transparent film based on a composite of polyvinyl alcohol (PVA) and caffeine was prepared for UV protection. The caffeine was extracted from ground coffee without any further purification process; in parallel, a 5.00 wt.% aqueous PVA solution was prepared. From this solution, PVA solutions with different concentrations of the extracted caffeine were prepared. The polymeric films were prepared by spin-coating deposition onto a borosilicate glass substrate. UV-Vis spectroscopy revealed that the film with 1.00 wt.% crude caffeine showed protective UV properties with approximately 43.27% absorption of the total incident radiation. The film with high concentration (5.00 wt.%) showed a similar absorption ability, but it was very brittle. On the other hand, ATR-FTIR spectroscopy showed a significant decrease in OH band absorption with the addition of 1 wt.% crude caffeine, implying that the amorphous and crystalline regions of PVA interact with caffeine molecules through hydrogen bonds, up to saturation. This study suggests the correct incorporation of caffeine within the polymeric matrix. X-ray diffraction analysis suggests that the α-phase of caffeine is complexed in the compound, however the disappearance of the characteristic [1-12] peak indicates the formation of caffeine clusters with a preferred orientation along the [110] planes. It is also confirmed that the most amorphous film was the one with 1.00 wt.% caffeine, with a crystallinity degree of approximately 14.82%. With respect to the polymeric film prepared from the 1% aqueous caffeine solution, XPS spectroscopy showed a real caffeine concentration of approximately 0.94%, impurity level of 9.61% and humidity level of 36.7%. Finally, SEM micrographs showed laminar structures of caffeine on the PVA justifying the formation of caffeine complexes along [110] direction.